STUDI DATA BASE DAN ANALISIS PEMETAAN KEMISKINAN DAN PENGANGGURAN DI KABUPATEN BUTON - Ahmad Ahmad; La Tondi La Tondi (JEP (Jurnal Ekonomi Pembangunan), 2018)
This study aims to: (1) find out data on Buton district poverty and unemployment; and (2) knowing the poor population and unemployment in Buton Regency. Data analysis using descriptive qualitative data reduction, data presentation, and conclusion. The results showed that: (1) the population and poor households were relatively high, the level of education and skills was low, the number of dependents was high, the income level was low, the ownership of factors was low, the intervention of poverty alleviation programs was not well targeted, poor households do not use high clean water, poor people do not work relatively much, the condition of emergency housing and very emergency, treatment at the dukun and self treatment are relatively large, do not have family latrines, the source of poverty is poor structural (40.94%), cultural (41, 19%), voluntary poor (10.62%) and natural poor (1.25%); and (2) the number of unemployed people is relatively high, education and skills are low, job vacancies are limited, employment information is limited, capital and coaches are lacking.